Konopie siewne i ich zastosowanie ze współczesnej geriatrii = Cannabis sativa and their use of modern Geriatrics - Emilia Główczewska-Siedlecka; Katarzyna Madra-Gackowska; Krystyna Nowacka; Kornelia Kędziora-Kornatowska (Kazimierz Wielki University, 2016)
Główczewska-Siedlecka Emilia, Madra-Gackowska Katarzyna, Nowacka Krystyna, Kędziora-Kornatowska Kornelia. Konopie siewne i ich zastosowanie ze współczesnej geriatrii = Cannabis sativa and their use of modern Geriatrics. Journal of Education, Health and Sport. 2016;6(10):34-39. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.159640 http://ojs.ukw.edu.pl/index.php/johs/article/view/3922       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 08.10.2016.         Konopie siewne i ich zastosowanie ze współczesnej geriatrii Cannabis sativa and their use of modern Geriatrics   Główczewska-Siedlecka Emilia1, Madra-Gackowska Katarzyna1, Nowacka Krystyna2, Kędziora-Kornatowska Kornelia1  1.      Katedra i Klinika Geriatrii, Collegium Medicum im. L. Rydygiera w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu 2.      Katedra i Klinika Rehabilitacji, Collegium Medicum im. L. Rydygiera w Bydgoszczy, Uniwersytet Mikołaja Kopernika w Toruniu      Streszczenie   Konopie należą do jednych z najdawniej uprawionych roślin i znane są również jako znamienny środek psychoaktywny dzięki zawartości delta 9-tetrahydrokanabinolu (THC), który jest substancją o działaniu psychotropowym a także przeciwzapalnym i przeciwbólowym. Dlatego konopie mogą znaleźć zastosowanie u chorych ze schorzeniami układu nerwowego oraz  chorych w wieku podeszłym. Niezależnie od powszechnej w społeczeństwie pejoratywnej stygmatyzacji konopi kojarzonej z marihuaną, należy podkreślić potencjalnie bardzo korzystne działanie konopi u odpowiednio dobranych chorych.   Słowa kluczowe: konopie siewne, geriatria, kannabinoidy       Abstract Hemps belong to one of most formerly cultivated plants and they are also characteristic due to contents THC, which has anti-inflamatory, analgetic and psychotropic activity. So hemps can find appliance in patient with neurological dissorders and geriatric patients. Independently on general pejorative opinion associated with marijuana hemps, its potential beneficial activity seems to be hopeful in some patients.   Key words: hemps, geriatry, cannabinoids